PENGARUH PELAKSANAAN PROGRAM KELUARGA HARAPAN TERHADAP KESEJAHTERAAN KELUARGA MISKIN DI KELURAHAN BOJONG SARI KOTA DEPOK - Anita Claudia; Adi Fachrudin (Universitas Muhammadiyah Jakarta, 2017)
This research is conducted on the basic of the presence of poverty in Indonesia, especially in Kelu- rahan bojong sari Depok. in an effort to overcome poverty, the government has various poverty reduction program. one of the program is the hope family program. The purpose of this study is to determine the welfare of the poor family, the respondents chosen are 50 respondents of the poor family as receiver of the hope family program and 50 respondents of the poor family who didn’t get aid of the hope family program . By test analysis used is Mann Whitney U test. The result suggests that the poor family don’t get an aid program of the hope family program more prosperous as physical and economical than the poor family who receive aid program of hope family . on the dimension of the psychological welfare and the subjective welfare of the second of category of the poor family don’t have the difference. Therefore, the implementation of hope family program located on the study does not have a significant impact for program participants. Therefore, it is recommended in order to be con- ducted an evaluation of the implementation of the hope family program located on the study